Diagnosa Penyakit Ikan Menggunakan Sistem Pakar - Suwarsito Suwarsito; Hindayati Mustafidah (JUITA : Jurnal Informatika, 2011)
Background from this research is too much of disease case groaning fish in Indonesia. Most farmers feel to confuse to look for various possible solutions. Reading of reference books and or visit upon the expert of fish disease likely not possible because that too much need time and energy and also expense, whereas fish which is being come down have to be immediately handled. According to the mentioned, this research develops an expert system which can be a consultant that capable to diagnose in fish disease cause and can give an advice to overcome the disease. This Expert system is called FISHEXP. This research is a development study, whichoperationally steps are: knowledge acquisition, knowledge representation using backward chaining, making shell in a computer program using Borland C++ programming language, and system examination.FISHEXP developed for 6 forms composed by 1 main form and 5 child forms for consultancy, adding rules, displaying rules on computer monitor, showing what that system FISHEXP is, and give the explanation of how to operate it. There are 3 main menus in FISHEXP that represent a user interface between user and the system. Among the menus, Consultancy is the prime menu cause shows the work of the FISHEXP system